Study on Exoskeleton Mechanical System based on Pull and Push Flexible Shaft Drive - Hua Fuhu; Wang Guoqing; Yang Siqi; Liang Sirui; Qu Qifeng (Jixie chuandong)
Facing with the urgent need of tools for the elderly and disable,which is brought by the rapid increase in the number of the elderly in recent years,plan to design an exoskeleton-assisted robot from a bionic angle. After determining the use of a push-pull flexible shaft to drive a motion joint,the design of mechanism and structure of shoulder and elbow joint of exoskeleton robot is completed first. Then the ankle joint and other flexible drive are designed,and the activity range of each joint is analyzed. Finally,the dynamics analysis of the leg joint and the foot joint and kinematics analysis of robot’s gait are carried out in the dynamics simulation software. In summary,as a kind of assist tool for the elderly and disable,the robot can meet the requirements of motion smoothness and speed stability.